Analysis of the Sustainability of the Charcoal Business in Firdaus Village, Bilah Hulu District, Labuhan Batu Regency - Harahap, Yeni Marlina; Yusrizal, Yusrizal; Dharma, Budi (Trunojoyo University of Madura, 2024)
One of the rubber wood derivative products that can be used as a product is charcoal, and charcoal has promising business potential and can be developed. This research aims to construct strategies that can be used by wood charcoal entrepreneurs to improve their business. Using a qualitative approach, the research focus is charcoal business owners, sellers and consumers. The analysis tool used is SWOT to recommend strategies. The analysis results show that the wood charcoal industry is in quadrant 1 of the SWOT diagram, which shows an aggressive business continuity strategy by utilizing strength and opportunity (S-O) factors. From the research results, the recommended strategy includes increasing business experience, increasing production capacity, and product development to expand business networks. These steps are expected to ensure the sustainability and growth of the wood charcoal business in Firdaus Village, by maximizing internal strengths and external opportunities and facing various existing challenges effectively.